The Structure of the Cost of Capital Under Uncertainty - Beja, A. (Review of Economic Studies, 1971)
Journal Article The Structure of the Cost of Capital under Uncertainty Get access A. Beja A. Beja Tel Aviv University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 359–368, https://doi.org/10.2307/2296388 Published: 01 July 1971